FUTURE PERCEPTIONS OF ART EDUCATION TEACHERS IN SECONDARY SCHOOLS IN THE CENTER OF GOVERNORATE OF BABIL - Sukaina Hasan Khayif (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study aimed to measure the future perceptions of art education teachers about the future of their profession and the reality of art education in secondary schools, as well as trying to identify the difference between those perceptions between male and female teachers, and to achieve this, the researcher prepared a scale for those future perceptions, the paragraphs of which amounted to (20) paragraphs, After confirming its validity and stability, it was applied to the basic research sample of (60) teachers and one of those working in secondary schools in the center of Babel Governorate .